Transformation of Educational Intitutional in the Muhmmadiyah Organization - Kurniawan, Desma; Maksum, Muh. Nur Rochim; Mustofa, Triono Ali (Universitas Muhammadiyah Surakarta, 2023)
Muhammadiyah is one of the largest Islamic Organizations in Indonesia, which carries out da'wah amar ma'ruf nahi munkar with the aim and purpose of upholding Islam. One of Muhammadiyah's roles in Indonesia is establishing educational institutions that adhere to Islamic religious values with a school system combining religious and general knowledge, which has now developed into Pesantren. Pesantren has become the main witness to the spread of Islam in Indonesia which functions to prepare santri who study and master in Islamic education, known as Tafaqquh fiddin, which is expected to be able to produce a good generation and participate in educating Indonesian society through Islamic Da'wah and become a stronghold for the people. This encourages the Muhammadiyah Organization to continue advancing and developing education. This study aims to describe the transformation of educational institutions in the Muhammadiyah Organization starting with the school system and now developing into pesantren. This research uses library research methods with historical, sociological, and descriptive approaches. The data collection methods used were observation and documentation. The results of the study stated that the Muhammadiyah Educational Institution has been moving since its inception until it has been transformed into a Pondok Pesantren Institution with various models such as Islamic Boarding Schools with Madrasah system, Takhassus system, and Muhammadiyah Boarding School system.